Meta-Analysis of Diagnostic Performance of Contrast-Fractional Flow Reserve versus Quantitative Flow Ratio for Functional Assessment of Coronary Stenoses - Ruitao Zhang; Jianwei Zhang; Lijun Guo (Journal of Interventional Cardiology)
Background. Use of the fractional flow reserve (FFR) technique is recommended to evaluate coronary stenosis severity and guide revascularization. However, its high cost, time to administer, and the side effects of adenosine reduce its clinical utility. Two novel adenosine-free indices, contrast-FFR (cFFR) and quantitative flow ratio (QFR), can simplify the functional evaluation of coronary stenosis. This study aimed to analyze the diagnostic performance of cFFR and QFR using FFR as a reference index. Methods. We conducted a systematic review and meta-analysis of observational studies in which cFFR or QFR was compared to FFR. A bivariate model was applied to pool diagnostic parameters. Cochran’s Q test and the I2 index were used to assess heterogeneity and identify the potential source of heterogeneity by metaregression and sensitivity analysis. Results. Overall, 2220 and 3000 coronary lesions from 20 studies were evaluated by cFFR and QFR, respectively. The pooled sensitivity and specificity were 0.87 (95% CI: 0.81, 0.91) and 0.92 (95% CI: 0.88, 0.94) for cFFR and 0.87 (95% CI: 0.82, 0.91) and 0.91 (95% CI: 0.87, 0.93) for QFR, respectively. No statistical significance of sensitivity and specificity for cFFR and QFR were observed in the bivariate analysis (P=0.8406 and 0.4397, resp.). The area under summary receiver-operating curve of cFFR and QFR was 0.95 (95% CI: 0.93, 0.97) for cFFR and 0.95 (95% CI: 0.93, 0.97). Conclusion. Both cFFR and QFR have good diagnostic performance in detecting functional severity of coronary arteries and showed similar diagnostic parameters.